2011
DOI: 10.1175/2011jas3705.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Response of the South Asian Monsoon Trough to Latent Heating from Stratiform and Convective Precipitation

Abstract: Simulation experiments using a simplified atmospheric GCM and supplementary diagnostic analyses of observations are performed to understand how the South Asian monsoon trough (MT) responds dynamically to latent heating from mesoscale convective systems (MCSs). Observations reveal that the MT during active monsoons is characterized by a deep cyclonic vorticity extending from the surface to 350 hPa and organized MCSs covering over 3500-4000 km along the Indo-Gangetic plains. The MCSs during active monsoons are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 62 publications
3
66
0
Order By: Relevance
“…2). These findings are consistent with the results of previous studies showing that the stratiform rain coincides with higher total precipitation values (Romatschke and Houze, 2011;Dey Choudhury and Krishnan, 2011). one explanation for the poorer correlation during the break phase may be due to the fact that the cloudiness over the CMR region during the break phase results from short-lived thunderstorms.…”
Section: Variation Of Cloud Pattern During Active and Break Phasesupporting
confidence: 92%
See 1 more Smart Citation
“…2). These findings are consistent with the results of previous studies showing that the stratiform rain coincides with higher total precipitation values (Romatschke and Houze, 2011;Dey Choudhury and Krishnan, 2011). one explanation for the poorer correlation during the break phase may be due to the fact that the cloudiness over the CMR region during the break phase results from short-lived thunderstorms.…”
Section: Variation Of Cloud Pattern During Active and Break Phasesupporting
confidence: 92%
“…TRMM precipitation radar observations as well as various field experiments indicate that these clouds are organized into Mesoscale Convective Systems (MCS) with a relatively higher abundance of stratiform-type precipitation (mostly nimbostratus) clouds (Houze and Churchill, 1987;Houze, 1989). Simulation experiments using an atmospheric GCM show that the CTCZ responds dynamically to latent heating from mesoscale convective systems (MCSs) which suggest that a stratiform-type heating profile is very efficient in promoting upward development of continental-scale cyclonic circulation well above the midtroposphere over the MT region during the active phase of the ISM (Dey Choudhury and Krishnan, 2011). over the west coast of India (WCI), the stratiform anomaly is negative (about -5%) off shore and positive (about +5%) over inland areas, and positive convective anomalies (about +5%) are observed during the active spell.…”
Section: Variation Of Cloud Pattern During Active and Break Phasementioning
confidence: 99%
“…The requirement of specifying lateral boundary conditions for RCM simulations poses restrictions in understanding the interactions between the large-scale summer monsoon circulation and the precipitation distribution over the South Asian region. For example, the monsoon rainfall activity over the Indo-Gangetic plains is closely related to the position and intensity of the Monsoon Trough (MT), as well as the strength of the large-scale southwesterly monsoon flow and the vigor of monsoon convection over the subcontinent (eg., Rao 1976, Alexander et al 1978, Das 1986, Krishnamurti and Bhalme, 1976, Krishnamurti and Surgi, 1987, Goswami et al, 2003, Joseph and Sabin 2008, Rajeevan et al 2010, Choudhury and Krishnan, 2011. Likewise, breaks in the monsoon rainfall over central India are characterized by a northward shift of the MT and heavy rainfall over the Himalayan foothills, and involve large-scale circulation anomalies such as the southward intrusions of mid-latitude westerly troughs into the Indo-Pak region, the formation of a blocking ridge over East Asia and the generation of circumglobal teleconnection patterns (e.g.…”
Section: Very High Resolution Global Gcms (Eg the Meteorological Rementioning
confidence: 99%
“…Tropical meso-scale convective systems (MCS) provide an important link between organized cumulus convection and largescale motion (Houze, 2004). In a recent study, Choudhury and Krishnan (2011) pointed out that latent heating from organized MCS over the MT region can effectively promote the upward development of continental-scale cyclonic circulation well above the mid-tropospheric levels. Figure.8d shows the vertical profiles of relative vorticity (ζ) averaged over the MT region from ERA (green), the zoom (blue) and no-zoom (purple) simulations.…”
Section: Moist Processes Over the Mt Regionmentioning
confidence: 99%
“…The second point is related to the heat low and monsoon trough which are important semi-permanent features of the South Asian monsoon (e.g. Sikka and Narasimha, 1995;Wang, 2004;Bollasina and Nigam, 2010;Ayantika and Krishnan, 2011). Studies have shown that cyclonic circulation associated with southward intrusion of mid-latitude westerly troughs over the western end of the monsoon trough together with moisture inflow from the Arabian Sea can favour increased convective activity locally Wang, 2005, 2007;Saeed et al, 2010Saeed et al, , 2011Hong et al, 2011).…”
Section: Datamentioning
confidence: 99%